2016
DOI: 10.1007/s40620-016-0297-2
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast as an add-on treatment in steroid dependant nephrotic syndrome, randomised-controlled trial

Abstract: Our findings highlight the effect of montelukast on renal function, but suggest that the clinical and laboratory efficacy of the addition of montelukast to steroids in maintenance treatment of SDNS is debatable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The role of LTs in glomerular injury has also been demonstrated in the nephrotoxic serum-induced glomerular injury model, due to increased recruitment/activation of polymorphonuclear cells and increased LTB 4 production in the kidney, which eventually amplifies the reduction of glomerular filtration rate [156]. Moreover, LTB 4 and LTC 4 /D 4 /E 4 levels are both increased in patients with nephrotic syndrome (NS), and this may be the reason why the serum creatinine, diastolic blood pressure, and protein/creatinine ratio of patients are significantly reduced [157].…”
Section: Mechanism Of Aa-induced Renal Inflammationmentioning
confidence: 99%
“…The role of LTs in glomerular injury has also been demonstrated in the nephrotoxic serum-induced glomerular injury model, due to increased recruitment/activation of polymorphonuclear cells and increased LTB 4 production in the kidney, which eventually amplifies the reduction of glomerular filtration rate [156]. Moreover, LTB 4 and LTC 4 /D 4 /E 4 levels are both increased in patients with nephrotic syndrome (NS), and this may be the reason why the serum creatinine, diastolic blood pressure, and protein/creatinine ratio of patients are significantly reduced [157].…”
Section: Mechanism Of Aa-induced Renal Inflammationmentioning
confidence: 99%
“…(2020) 10:1490 | https://doi.org/10.1038/s41598-020-58463-z www.nature.com/scientificreports www.nature.com/scientificreports/ The effect of cetirizine or montelukast on corticosteroid dependency or relapse in MCNS patients have not been described thus far. Zedan et al 29 conducted a randomized control study in childhood-onset nephrotic syndrome patients to determine if montelukast has beneficial effects on idiopathic nephrotic syndrome, but they did not evaluate renal biopsies, corticosteroid dosage, and relapse profiles. Instead, they showed that plasma leukotriene B4 and LTC4/D4/E4 were significantly decreased by montelukast treatment 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Zedan et al 29 conducted a randomized control study in childhood-onset nephrotic syndrome patients to determine if montelukast has beneficial effects on idiopathic nephrotic syndrome, but they did not evaluate renal biopsies, corticosteroid dosage, and relapse profiles. Instead, they showed that plasma leukotriene B4 and LTC4/D4/E4 were significantly decreased by montelukast treatment 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In view of the relatively large number of promising preclinical studies and availability of leukotriene inhibitors as approved drugs, it is frustrating to find out that only one clinical study, evaluating the role of leukotrienes in a renal diseases, was reported, and reaching an inconclusive outcome. In that study, treatment of children having primary nephrotic syndrome with montelukast on top of steroids did not provide a clear benefit [ 42 ▪ ]. Properly designed clinical trials using leukotriene inhibitors are required for evaluating their potential use in attenuating nephrotoxicity of drugs such as cyclosporine, gentamycin, alderonate, methotrexate and amikacin.…”
Section: Discussionmentioning
confidence: 99%